Validity of quantitative assessment of posterior pelvic tilt and contralateral vaulting in hemiplegia using 3D treadmill gait analysis. Issue 2 (17th February 2021) - Tanikawa, Hiroki; Inagaki, Keisuke; Ohtsuka, Kei; Matsuda, Fumihiro; Mukaino, Masahiko; Yamada, Junya; Kanada, Yoshikiyo; Kagaya, Hitoshi; Saitoh, Eiichi
ABSTRACT: Background: Assessing abnormal gait patterns could indicate compensatory movements, which could be an index for recovery and a process of motor learning. To quantify the degree of posterior pelvic tilt, contralateral vaulting is necessary. Objectives: This study aimed to develop and evaluate the validity of quantitative indices for posterior pelvic tilt and contralateral vaulting in hemiplegic patients. Methods: Forty-six healthy control subjects and 112 hemiplegic patients participated in this study. Of the 112 patients, 50 were selected into each abnormal gait pattern group, with some overlap. Three experienced physical therapists observed their walking and graded the severity of the two abnormalities in five levels. An index to quantify each of the two abnormal gait patterns was calculated from the three-dimensional treadmill gait analysis. The index values of patients were compared with those of healthy subjects and with the results of observational gait assessment done by three physical therapists with expertise in gait analysis. Results: The index values were significantly higher in hemiplegic patients than in healthy subjects (28.0% and 44.7% for the posterior pelvic tilt in healthy subjects and patients, respectively and 0.9 and 4.7 for the contralateral vaulting, respectively). A strong correlation was observed between the index value and the median observational rating for two abnormal gait patterns (r = −0.68 and −0.72). Conclusions: The proposed indices for posterior pelvic tilt and contralateral vaulting are useful for clinical gait analysis, and thus encouraging a more detailed analysis of hemiplegic gait using a motion analysis system.